Sistem Informasi Pengarsipan Surat Berbasis Website Pada Dinas Koperasi UMKM Perdagangan dan Perindustrian Kabupaten Cianjur - Fajriati, Dhila Rakhma; Maulana, Haisyam (LPPM STIKOM Tunas Bangsa, 2024)
Advances in information technology have created changes in the management of various aspects in various sectors, including letter archiving. In this context, this research aims to overcome the challenges of manual letter filing at Department of Cooperatives for Micro, Small and Medium Enterprises, Trade and Industry, Cianjur Regency. This research proposes a web-based application development method using the Laravel framework with a focus on storing, searching and managing mail. The main feature is to make it easier to quickly search for letters and provide convenience in archiving processing. It is hoped that the application of this application can provide an effective solution to the challenges of letter archiving at Department of Cooperatives for Micro, Small and Medium Enterprises, Trade and Industry, Cianjur Regency, as well as contribute to the development of information technology in the field of letter archiving.